2021
DOI: 10.5194/hess-25-5219-2021
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Unresolved aspects of the direct vapor equilibration method for stable isotope analysis (<i>δ</i><sup>18</sup>O, <i>δ</i><sup>2</sup>H) of matrix-bound water: unifying protocols through empirical and mathematical scrutiny

Abstract: Abstract. The direct vapor equilibration laser spectrometry (DVE-LS) method has been developed for obtaining matrix-bound water stable isotope data in soils, the critical zone, and bedrock, deriving therefrom subsurface water flow and transport processes and, ultimately, characterizing, for example, groundwater recharge and vulnerability. Recently, DVE-LS has been increasingly adopted due to its possible high sample throughput, relative simplicity, and cost-efficiency. However, this has come at the cost of a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 55 publications
3
34
1
Order By: Relevance
“…The amounts of the present study were based on Millar et al ( 2018), and we used 5 g of leaves, 5 g of stems and twigs, 3 g of roots and 3 g of fruit sample. We agree with previous suggestions (Gralher et al, 2021;Hendry et al, 2015;Wassenaar et al, 2008) that researchers should not aim at collecting a certain standard sample volume or weight but instead collect samples containing a minimum volume of water necessary to equilibrate the bag's headspace. Wassenaar et al (2008) and Hendry et al (2015) suggested a minimum of 3 ml, which was based on observations using 1 L doublefreezer-bagged samples of various artificially produced moisture contents.…”
Section: Operating Proceduressupporting
confidence: 90%
See 2 more Smart Citations
“…The amounts of the present study were based on Millar et al ( 2018), and we used 5 g of leaves, 5 g of stems and twigs, 3 g of roots and 3 g of fruit sample. We agree with previous suggestions (Gralher et al, 2021;Hendry et al, 2015;Wassenaar et al, 2008) that researchers should not aim at collecting a certain standard sample volume or weight but instead collect samples containing a minimum volume of water necessary to equilibrate the bag's headspace. Wassenaar et al (2008) and Hendry et al (2015) suggested a minimum of 3 ml, which was based on observations using 1 L doublefreezer-bagged samples of various artificially produced moisture contents.…”
Section: Operating Proceduressupporting
confidence: 90%
“…Wassenaar et al (2008) and Hendry et al (2015) suggested a minimum of 3 ml, which was based on observations using 1 L doublefreezer-bagged samples of various artificially produced moisture contents. Gralher et al (2021) calculated the minimum necessary absolute water content to be 1.47 ml when using evaporation-safe bags of 1 L headspace volume. Their suggested minimum volume accounts for the fact that depending on the equilibration temperature a defined amount of sample water will evaporate to saturate a given bag's headspace.…”
Section: Operating Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass vials with polypropylene (PP) screw caps, thickwalled HDPE bottles, and perfluoroalkoxy-teflon (PFA) containers all preserved the original sample isotope values (Böttcher & Schmiedinger, 2021;Spangenberg, 2012). Other research assessed storage media choices and equilibration times for the direct vapour equilibration-IRIS approach (DVE-IRIS) (Gralher et al, 2021). They transmission rates of 0.07 cm 3 /m 2 /day (Schwab et al, 2016).…”
Section: Process Chain Optionsmentioning
confidence: 99%
“…Freezing or cooling samples during transport and storage is thought to mitigate temperature related fractionation effects, limit sample decomposition, limit generation of reducing environments, and reduce microbial activity (typically an issue in soils) which thereby limits CO 2 buildup (Fischer et al, 2019;Gralher et al, 2021). For IRIS analysers, changes in the gas matrix (i.e., caused by CO 2 build up), can affect measured isotopic values (Gralher et al, 2016(Gralher et al, , 2021. However, freezing samples may destroy soil microstructures (Gralher et al, 2021), and causes bursting of cell walls in plant samples (Fischer et al, 2019;Millar et al, 2018).…”
mentioning
confidence: 99%